Analysis of Vibration Characteristics in 17-Inch Aluminum Alloy Wheel Rims Using Finite Element Method - Wijaya, Victor Indra; Ariyansah, Riyan; Agusman, Delvis; Rifky; Heriyani, Oktarina (Fakultas Teknik Universitas Pancasila, 2024)
The wheel rim serves as a component designed to provide stability and necessary support for vehicle tires. The phenomenon of resonance occurring when the external vibration frequency approaches the natural frequency of the structure has the potential to increase vibration amplitude, which can lead to wheel rim damage. This study aims to investigate the shape patterns and natural frequencies of 17-inch aluminum alloy wheel rims, as well as to analyze the maximum total deformation that occurs. The finite element method is employed to simulate the vibration characteristic of 17-inch aluminum alloy wheel rims under various natural frequencies. Modifications to the wheel rim design are made by altering the spoke angle in variations of 5°, 10°, and 15°. The vibration characteristic data of the wheel rim was obtained through simulation using ANSYS software. The research findings indicate that the natural frequencies range from approximately 364.7 Hz to 723.21 Hz. Furthermore, the maximum total deformation values range from approximately 9.7 mm to 22.5 mm.